Comparison of Outcome of Lactose-Free Formula Milk with Yogurt in Children with Acute Diarrhea - Mahjabeen Akram, Sadam Hussain, Muhammad Wasim Salim, Faiza Pervaiz, Sumera Abdul Karim, Humayun Iqbal Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Diarrhea is one of the most common problems in Pakistan where Khyber Pakhtunkhwa has the maximum prevalence i.e, 28% followed by Sindh (23%), Punjab (22%), and Baluchistan (12%). According to WHO every year 1.5 million children under 5 years, die just because of diarrhea. Therefore, this study aimed to look at the effect of lactose-free formula milk versus homemade plain yogurt in children with acute diarrhea. Methods: A randomized controlled trial was carried out on 60 children of age 4-24 months, 30 in each group in the Department of Pediatrics, Services Hospital Lahore. Group 1 was given yogurt while lactose-free milk was given to group 2. The duration of resolution of diarrhea was noted in hours and data was statistically analyzed using SPSS version 20. Practical Implication: The practical implication of comparing lactose-free formula milk with yogurt as a dietary intervention for children with acute diarrhea involves several considerations. Firstly, the severity and duration of diarrhea should be evaluated to determine the appropriate intervention. Secondly, the age and nutritional needs of the child should be taken into account. Thirdly, the availability and acceptance of lactose-free formula milk and yogurt in the local context should be considered. Additionally, the potential benefits and drawbacks of each option, such as the nutritional content, ease of digestion, and probiotic properties of yogurt, need to be assessed. It is important to consult with healthcare professionals and make an informed decision based on the specific circumstances to promote optimal outcomes in managing acute diarrhea in children. Results: Out of 60 children, 26 (43.33%) were male and 34 (56.67%) were female. In groups 1 and 2, the mean duration of resolution of diarrhea (outcome) was 43.9 ± 7.30 hours and 71.57 ± 12.92 hours respectively. Group 1 patients’ treatment showed a significant difference in the outcome than group 2 patients (P value= 0.00). However, the treatment effect on gender was found non-significant (P value= 0.48). The outcome in females was 43.6 ± 7.5 hours with yogurt and 70.6 ± 8.4 hours with lactose-free milk while in males the outcome was 44.3 ± 8.6 hours with yogurt and 73.1 ± 9.1 hours with lactose-free milk. Conclusion: The use of yogurt is better than lactose-free formula milk for the resolution of diarrhea. Keywords: Lactose-free formula milk, homemade plain yogurt, diarrhea.